Comparative analysis of database mapping frameworks available in NuGet Manager - Klimiuk, Maciej; Karabowicz, Paweł; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2024)
Every year amount of data significantly grows. This causes a need of tools capable of processing data as quickly as possible. The aim of this article is to perform a comparative analysis of ORM (Object Relational Mapping) tools available in the NuGet manager. The comparison of tools was carried out on two relational database management systems, PostgreSQL and MySQL. Each tool performed eight DML operations, including SELECT, INSERT and UPDATE operations. The operations were repeated 1, 10, 100, 1000, and 10,000 times, respectively. The execution time of each query was measured using the system StopWatch class available in the .NET environment. The results showed that the best ORM tool turned out to be Dapper.